Greenland, view of Kjerulf Fjord through to Dicksons Fjord annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Through to Dickson [Dicksons] Fjord. In background mountains forming western side of Hisinger glacier [Hisinger Gletscher] in Unknown Valley. Here they start to become the western side of Left Valley at its S.E terminal. In the foreground, Hisinger Glacier [Hisinger Gletscher] at the northern most end of Unknown Valley and at what I call The Divide. The surface of the glacier is entirely covered with sharp-pointed hummocks and crevasses; the side facing me terminated in dark soil and stones which showed no effect of grinding or tearing out of the land. Photo taken from slope of southern terminal of mts. [mountains] forming eastern side of Kjerulfs [Kjerulf] Fjord, looking S.W.